Compositional effects on the ignition and combustion of low octane fuels under diesel conditions. (15th May 2018) - Jain, Siddharth K.; Aggarwal, Suresh K.
Highlights: Fundamental research on the ignition and combustion of low-octane/low-cetane fuels in direct injection engines. Effects of fuel sensitivity and RON (research octane number) on the ignition and combustion of naphtha fuel surrogates. Binary and ternary blends with RON = 80 and 90, and varying amounts of iso-octane, n-heptane, and toluene investigated. Simulations performed for ignition in homogeneous mixtures, and for ignition and flame structure in 3-D liquid fuel sprays. Two-stage ignition, spray flame structure, and liftoff length strongly modified by fuel sensitivity and RON. Abstract: The amount of non-paraffinic components is directly associated with fuel sensitivity (S), which is an important property for using low-octane and low-cetane fuels in direct injection engines. In this paper, we examine the effects of S and RON (research octane number) on the ignition and combustion behavior of naphtha fuel surrogates in homogeneous mixtures and diesel sprays. Two binary blends (PRF70 and PRF80) and four ternary blends (TPRF70-a, TPRF70-b, TPRF80-a, TPRF80-b), with varying amounts of iso-octane, n-heptane and toluene, are considered. Simulations are performed using a reaction mechanism with 109 species and 543 reactions. The mechanism is validated against the shock tube and rapid compression machine ignition data, and non-reacting spray data. Ignition simulations in homogeneous mixtures are performed using CHEMKIN-Pro for temperature range of 625–1250 K, equivalence range of ɸ = 0.5–2.0, and pressure of 55 bar. The study is then extended to examine the transient ignition and flame structure in liquid fuel sprays in a constant-volume combustion vessel using the CFD software CONVERGE. Results indicate that the temperature dependence of ignition characteristics in both homogeneous mixtures and sprays is strongly influenced by fuel sensitivity. In particular, it affects the NTC behavior and temperature dependence of the 1st and 2nd stage ignition processes. The ignition kernel structure in sprays is also strongly modified by fuel sensitivity, as the ignition kernel in ternary sprays involves richer mixtures, while that in binary sprays contains near stoichiometric mixtures. Consequently, the spray flame structure is also modified by fuel sensitivity. While the spray flame is characterized by partially premixed combustion involving a lean premixed zone (LPZ), a rich premixed zone (RPZ), and a nonpremixed zone (NPZ), the effect of sensitivity is to enhance the relative contribution of RPZ compared to those of NPZ and LPZ. In addition, due to enhanced ignitability, the flame in ternary sprays is located closer to the injector compared to that in binary sprays. The effect of higher RON is to increase the ignition delay time. Consequently, the ignition kernel involves relatively leaner mixtures, and the flame structure is characterized by increased contributions from LPZ compared to RPZ, and the flame liftoff length is increased. Increasing the initial reactor temperature has the opposite effect. A sensitivity analysis is performed to identify reactions that characterize the reduced and enhanced ignitability of ternary blends at low and high temperatures, respectively.